CREATING THE KNOWLEDGE SET OF DEVELOPMENT OF LEARNING INDIVIDUAL BEHAVIORS ACCORDING TO THE SIX CARITA IN THE TIPITAKA - Srivichai , Suddhipong; Suwanprateep, Thanee; Koomkrong, Viroj (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed to 1) study the development of learning behaviors according to the 6 temperaments, 2) create a knowledge set on the development of learning behaviors of individuals according to the 6 temperaments, and 3) propose the creation of a knowledge set on the development of learning behaviors of individuals according to the 6 temperaments in the Tripitaka. This was a qualitative field research by collecting data from documents and in-depth interviews with 15 key informants. The data were analyzed in terms of content. The research results found that 1) the development of learning behaviors of individuals according to the 6 temperaments in the Tripitaka consisted of people with Rga-carita: one of lustful temperament, people with Dosa-carita: one of hating temperament, people with Moha-carita: one of deluded temperament, people with Saddh-carita: one of faithful temperament, people with Buddhi-carita: one of intelligent temperament, people with Vitakka-carita: one of speculative temperament. 2) The creation of a knowledge set on the development of learning behaviors of individuals according to the 6 temperaments consisted of people with Rga-carita: one of lustful temperament, such as the cases of Phra Nanda and Phra Khema Theri. Dosa-carita was a person whose behavior tended to be hot-tempered and easily angered, such as the case of the glass carpenter. Moha-carita was a person whose behavior tended to be foolish, think less and lazy, such as the case of the Thandaki Forest. Saddh-carita was a person with gullible, such as the case of the Venerable Vakkali. Buddhi-carita was a person who liked to use wisdom, intelligent, having quick wit, such as the cases of a graduated novice. Vitakka-carita was a person with anxious and fearful, such as a case study of Nakkhatta Jataka. 3) A set of knowledge on the development of learning behavior of individuals according to the 6 temperaments in the Tripitaka, consisting of the development of learning behavior of individuals, people with Rga-carita should develop Asubha and Kyagatsati. People with Dosa-carita should develop Kasiṇa and Brahmavihra. People with Moha-carita should develop nāpānasati. People with Saddh-carita should develop the 6 Anussati. People with Buddhi-carita should develop Maraṇasati, Upasamanusati, hārepaṭikūlsaññā. People with Vitakka-carita should develop nāpānasati.